THE PERCEPTIONS OF ROMANIAN YOUNG ENTREPRENEURS REGARDING THE CHALLENGES OF AN INNOVATIVE BUSINESS ENVIRONMENT - Lavinia DOVLEAC; Marius BĂLĂŞESCU; Simona BĂLĂŞESCU (Management & Marketing)
This paper aims the investigation of the relationship between entrepreneurial phenomenon among young people in Romania and the business environment, strongly marked by innovation and new technologies, as pillars of sustainable development in the knowledge-based society. For achieving the paper’s goal there are used the results of a qualitative research based on in-depth interview which aim to identify the views and experiences of young entrepreneurs on the advantages and disadvantages of starting an innovative business in Romania. Data analysis allowed the formulation of some recommendations to state institutions, business environment and the academic community to support young entrepreneurs in developing their business right after the launch. Access to new funding sources, guidance and informational support are the principal needs for entrepreneurs in their struggle to develop innovative sustainable businesses. The strong promotion of young entrepreneurs inside their community or at national level contributes to the development of a strong entrepreneurial culture for Romania.